Internalization of Multicultural Values in Building Unity snd Peace Amidst Diversity Among Students of Madrasah Ibtidaiyah Guntur Nusantara Denpasar - Savika, Helda Ivtari; Sholeh, Ahmad; Gafur, Abd. (Abjadia : International Journal of Education, 2025)
This study examines the internalization of multicultural values in Madrasah Ibtidaiyah (MI) Guntur Nusantara, Denpasar, Bali, which has a diverse student environment. Bali, which is rich in cultural, religious, and ethnic differences, is an important context for this study. This study aims to describe the multicultural values that are instilled, the process of internalization, and their impact on unity and peace in schools. This study uses a qualitative approach with a descriptive method. Data were collected through interviews with the principal, teachers, and students, as well as observations of student activities and interactions. The collected data were analyzed through data condensation, data presentation, and drawing conclusions. The results of the study indicate that multicultural values such as tolerance, mutual respect, cooperation, empathy, and social integration are internalized in MI Guntur Nusantara. This internalization is carried out through integration in the curriculum, extracurricular activities, school habits and culture, and teacher professional development. The impact of this internalization is increased student tolerance and openness, the creation of a harmonious school environment, and the realization of unity and peace amidst student diversity. This school has succeeded in making diversity a strength to build an inclusive and peaceful learning environment.